Relationship Obsessive–Compulsive Disorder: Interference, Symptoms, and Maladaptive Beliefs - Doron, Guy; Derby, Danny; Szepsenwol, Ohad; Nahaloni, Elad; Moulding, Richard (Frontiers in Psychiatry, 2016)
Background Obsessive preoccupation, doubts, and compulsive behaviors focusing on one’s romantic relationship and partner are receiving increasing clinical, theoretical, and empirical attention. Commonly referred to as relationship obsessive–compulsive disorder (ROCD), such symptoms have been linked with decreased relational and sexual functioning and lower mood, even after controlling for other obsessive–compulsive disorder (OCD) symptoms. To date, however, these symptoms have been studied in community samples alone. In the present study, we compared levels of interference, OCD, and mood symptoms between clinical participants with ROCD, OCD, and community controls. We also examined group differences in maladaptive beliefs previously linked with OCD and ROCD. Method Participants included 22 ROCD clients, 22 OCD clients, and 28 community controls. The Mini International Neuropsychiatric Interview was used to attain clinical diagnoses of OCD and ROCD. The Yale–Brown Obsessive–Compulsive Scale was used to evaluate primary-symptoms severity. All participants completed measures of symptoms and dysfunctional beliefs. Results ROCD clients reported more severe ROCD symptoms than the OCD and control groups. ROCD and OCD clients did not differ in severity of their primary-symptoms. ROCD clients scored higher than the other groups on maladaptive OCD-related and relationship-related beliefs. Finally, ROCD clients showed more severe depression symptoms than community controls. Conclusion ROCD is a disabling presentation of OCD that warrants research attention. Maladaptive OCD-related and relationship-related beliefs may be implicated in the development and maintenance of ROCD.